Reliability and statistics in transportation and communication : selected papers from the 17th International Conference on Reliability and Statistics in Transportation and Communication, RelStat'17, 18-21 October, 2017, Riga, Latvia /: selected papers from the 17th International Conference on Reliability and Statistics in Transportation and Communication, RelStat'17, 18-21 October, 2017, Riga, Latvia. ([2018]) - Unknown
No abstract available